Health information technology and optimizing workflow in a teaching hospital - Sajjad Dehghan; Ali Mohamamd Mosadeghrad; Alireza Atashi; Alireza Hajizadeh; Zeinab Khaledian; Maryam Tajvar (Payesh)
Objective(s): The implementation of health information systems in hospitals not only ensures more accurate record-keeping but also improves workflow. The aim of this study was to examine the workflow in the surgical department of Khatam Al-Anbiya Hospital in Behshahr, Iran and to provide health information technology-based solutions for improving health care process. Methods: This cross sectional study was conducted in 2022. The study included the following steps: mapping the workflow of surgical patients, time measurement and work measurement of processes, identifying existing infrastructure related to the processes, recognizing current issues, and proposing technology-based solutions. Data were collected using observation, interviews, and the Delphi method. Throughout different stages of the research, the participation of all stakeholders, including managers, staff, and patients, was secured. Additionally, a stopwatch was used for time measurement, and a data recording sheet was employed for work measurement. For quantitative data analysis, SPSS software and descriptive indices were utilized. Results: The existing problems in the workflow of the department included: "crowding of patients both in-person and via phone at the appointment scheduling section of the hospital," "delays in file formation," "retrieval of patient files," "confusion and delays in obtaining consent," "delays in providing paraclinical results," and "billing issues." To address these problems, IT-based interventions such as electronic scheduling, intelligent customer management systems, queue management, interactive voice response systems, and electronic health records were among the most significant recommendations provided. Conclusion: Planning for the enhancement of infrastructure based on health information technology and creating a framework for improving workflow in the surgical processes of the hospital, according to the current working environment, is necessary and should be prioritized by hospital management.